MANAJEMEN PENGEMBANGAN KARAKTER PESERTA DIDIK DI SMP NEGERI 36 MUKOMUKO - Sukarti Nengsih (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2022)
This research departs from the fact that there are still many students who have bad character and always violate school rules. The purpose of this study was to determine the planning of student character development, organizing student character development, implementing student character development and controlling student character development. This study used descriptive qualitative method. Data collection techniques through observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the research are: (1) character development planning in the form of applying character values to students, planning character development through extracurricular activities, making school regulations for students and teachers, and planning to make an honesty canteen: (2) organizing character development in the form of school principals dividing tasks according to their expertise, carry out unification of tasks by working together, and who are responsible for the teacher council and school principals; (3) the implementation of character development in the form of applying character values through the learning process, carrying out extracurricular in the application of character values, implementing school regulations and implementing teacher exemplary methods, and the honesty canteen has not been implemented because the costs are not sufficient (4) controlling character development in the form of determining achievement standards, evaluate by comparing the program implemented with the planned, make improvements to errors and make additions to deficiencies.